Paleoenvironmental context of Neanderthal occupations in northeastern Iberia: The small-mammal assemblage from Abric Romaní (Capellades, Barcelona, Spain) - Fernández-García, Mónica (2018)
The Abric Romaní site (Capellades, Barcelona, Spain) constitutes a key site for understanding the latest Neanderthal occupations in Western Europe. Here we present a comprehensive systematic and taphonomic analysis of a small-mammal assemblage from Level O of the Abric Romaní site, with the aim of reconstructing the paleoecological context in which the Neanderthals lived. The assemblage, which probably dates from a stadial episode between Interstadial 15 and Interstadial 14, contains fifteen small mammal species, including species uncommon for the northeast of Iberia, such as Sciurus vulgaris, Nyctalus lasiopterus and Pipistrellus pipistrellus. Taphonomic studies suggest a predatory origin for the assemblage, probably related to Strix aluco, and paleoecological inferences suggest lower temperatures (−3/−4 °C) and higher rainfall (+70/+170 mm) than at present and a landscape dominated by an open forest with watercourses. The new data improve our knowledge of trends associated with Marine Isotope Stage 3 that affected Neanderthal populations in the Iberian Peninsula, showing that the Neanderthals were well adapted to cooler and wetter conditions across Iberia.